Ultrathin corrosion-resistant water-based paint and preparation method thereof
Through chemical means such as phosphoric acid treatment and γ-aminopropyltriethoxysilane, a three-dimensional crosslinking network is built to ensure the uniform dispersion of zinc powder in the aqueous system, and a molecular-level crosslinking structure is formed through hyperbranched polyamide amine, which solves the contradiction between film thickness and corrosion resistance of traditional water-based coatings in the heavy corrosion protection field, and achieves long-term corrosion resistance and construction stability of ultra-thin coatings.
Patent Information
- Application Number
- CN202510390466.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-17
- Estimated Expiration
- 2045-03-31
AI Technical Summary
Traditional water-based epoxy coatings have contradictions between film thickness and corrosion resistance in the heavy anti-corrosion field, while ultra-thin coatings have problems such as poor dispersion stability of zinc powder, weak interface bonding and poor construction stability.
The zinc powder is treated with phosphoric acid to form a porous zinc phosphate layer, and Si-O-Zn covalent bond is formed by γ-aminopropyltriethoxysilane and graphene oxide to form a three-dimensional crosslinking network to ensure the uniform dispersion of zinc powder in the aqueous system. At the same time, hyperbranched polyamide amine is used to form a molecular-level crosslinked structure, enhancing coating adhesion and self-healing ability.
It realizes the long-term corrosion resistance of ultra-thin coating, reduces the electrostatic attraction of zinc powder, ensures the uniformity and adhesion of the coating, and significantly improves construction stability in harsh environments.
Smart Images

Figure CN120158185A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterborne coatings, and particularly relates to an ultra-thin corrosion-resistant waterborne coating and a preparation method thereof. Background Art
[0002] In the field of heavy corrosion protection, there is generally a contradiction between film thickness and corrosion resistance in traditional waterborne epoxy coatings. To meet the requirements of long-term protection, the coating thickness usually needs to be increased to more than 200 μm in the prior art. However, an overly thick coating film will not only increase the material cost but also lead to low construction efficiency, especially in the case of complex surface structures, defects such as sagging and pinholes are likely to occur. If a thin-layer coating (<100 μm) is used, the anti-permeability and mechanical strength of the coating will decrease significantly, and problems such as uneven dispersion of inorganic powder and weak interface bonding will be further aggravated, resulting in rapid penetration of corrosive media through the coating and causing matrix rust.
[0003] Commercially available ultra-thin waterborne coatings generally have poor dispersion stability of zinc powder: conventional mechanical dispersion is difficult to achieve uniform distribution of nano-scale zinc powder, and the accumulation of zinc powder in the thin layer forms a conductive path, which instead accelerates electrochemical corrosion. At the same time, the contact area between the resin and zinc powder in the thin-layer coating is small, and volume shrinkage during the curing process is likely to generate microcracks, and hydrolysis will occur at the interface in a humid and hot environment, resulting in coating peeling.
[0004] Although in the prior art, the penetration path of the medium can be extended by adding flaky fillers, when the filler content exceeds 15%, the viscosity of the coating will increase sharply. Although the modification of zinc powder with silane coupling agent can improve the interface bonding, it cannot meet the requirements of the long storage period of the waterborne system.
[0005] Therefore, how to obtain a waterborne coating with an ultra-thin thickness, long-term corrosion resistance and construction stability has excellent research prospects. Summary of the Invention
[0006] The purpose of the present invention is to solve the disadvantages existing in the prior art, and to provide an ultra-thin corrosion-resistant waterborne coating and a preparation method thereof.
[0007] An ultra-thin corrosion-resistant waterborne coating is composed of component A and component B in a mass ratio of 10:1 - 2; the raw materials of component A by mass include: 40 - 60 parts of waterborne epoxy emulsion, 30 - 50 parts of zinc powder, 1.2 - 3.6 parts of phosphoric acid, 1 - 3 parts of graphene oxide, 0.1 - 1 part of γ-aminopropyltriethoxysilane, 1 - 2 parts of dispersant, 0.1 - 1 part of defoamer, 1 - 3 parts of corrosion inhibitor, 0.1 - 1 part of leveling agent; the components of component B by mass include: 40 - 60 parts of curing agent, 1 - 3 parts of accelerator, 1 - 3 parts of hyperbranched polyamidoamine, 5 - 15 parts of cosolvent, 20 - 30 parts of water.
[0008] Preferably, the solid content of the aqueous epoxy emulsion is 45 - 55%, and the epoxy value is 0.1 - 0.2 mol / 100g.
[0009] Preferably, the dispersant is a polyether-modified silicone.
[0010] Preferably, the leveling agent is a fluorocarbon surfactant.
[0011] Preferably, the corrosion inhibitor includes ammonium molybdate.
[0012] Preferably, the accelerator is benzyldimethylamine.
[0013] Preferably, the cosolvent is dipropylene glycol butyl ether.
[0014] Preferably, the generation number of the hyperbranched polyamidoamine is 2.0 - 4.0 generations.
[0015] The preparation method of the above ultra-thin corrosion-resistant waterborne coating includes the following steps:
[0016] S1. Immerse zinc powder in an aqueous phosphoric acid solution, perform ultrasonic treatment at 40 - 50°C for 10 - 20 min, centrifuge, wash until neutral, dry in vacuum, and pulverize; add graphene oxide, γ-aminopropyltriethoxysilane, and water and mix, then ball mill for 1 - 2 h to obtain composite zinc powder;
[0017] S2. Preheat the aqueous epoxy emulsion to 40 - 50°C, adjust the pH value of the system to 8 - 9, add the composite zinc powder and the dispersant, raise the temperature to 60 - 65°C and continue stirring for 1 - 3 h, cool to room temperature, add the defoamer, corrosion inhibitor, and leveling agent and stir evenly, then filter to obtain Component A;
[0018] S3. Mix the curing agent, hyperbranched polyamidoamine, and accelerator evenly, add the cosolvent and water and perform ultrasonic treatment for 20 - 40 min to obtain Component B.
[0019] Preferably, in S1, the ultrasonic frequency is 35 - 40 kHz, and the ultrasonic power is 400 - 500 W; the ball milling speed is 150 - 250 r / min.
[0020] Preferably, in S3, the ultrasonic frequency is 30 - 40 kHz, and the ultrasonic power is 400 - 500 W.
[0021] The usage method of the above ultra-thin corrosion-resistant waterborne coating includes the following steps: Mix Component A and Component B evenly, spray on the area to be coated several times, with the film thickness per coating being 15 - 25 μm, and the total thickness of the obtained coating film being 60 - 75 μm, then bake and cure at 70 - 80°C.
[0022] Beneficial effects:
[0023] In the present invention, phosphoric acid treatment is adopted to generate a porous zinc phosphate layer on the surface of zinc powder. The silanol groups produced by the hydrolysis of γ-aminopropyltriethoxysilane combine with the hydroxyl groups on the surface of the phosphating layer to form Si-O-Zn covalent bonds. At the same time, the terminal amino groups thereof are bonded to the carboxyl groups of graphene oxide. Under the combined action, a three-dimensional crosslinked network is constructed, significantly reducing the electrostatic attraction between zinc powder particles, enabling the zinc powder to be uniformly dispersed in the aqueous system for a long time (storage period ≥ 6 months), and avoiding coating defects caused by sedimentation during construction.
[0024] In the present invention, the graphene sheets in the composite zinc powder form a dense physical barrier in the coating, greatly reducing the Cl- permeability. When the film thickness is only 75μm, the protective performance is better than that of the traditional 200μm coating. The chemical bonding between graphene and zinc powder can effectively inhibit interfacial phase separation and significantly enhance the coating adhesion.
[0025] In the present invention, the terminal amino groups of hyperbranched polyamidoamine undergo ring-opening reactions with epoxy groups to form a molecular-level crosslinked structure. At the same time, the unreacted amino groups combine with the composite zinc powder and can form coordination complexes with Zn2+ released by the corrosion of zinc powder, forming a self-repairing protective interface, which not only inhibits the further corrosion of zinc but also keeps the coating adhesion strength stable.
[0026] The present invention not only has good environmental protection but also can achieve long-term corrosion resistance when ensuring an ultra-thin thickness. At the same time, it has good construction stability and has significant application value in harsh environments such as ships and offshore wind power. Description of the Drawings
[0027] Figure 1 It is a comparison chart of the impact resistance and adhesion of the coating films prepared from the ultra-thin corrosion-resistant waterborne coatings obtained in Example 5 and Comparative Examples 1-2.
[0028] Figure 2 It is a comparison chart of the self-repair rate of the coating films prepared from the ultra-thin corrosion-resistant waterborne coatings obtained in Example 5 and Comparative Examples 1-2. Detailed Embodiments
[0029] The present invention will be further illustrated below in conjunction with specific embodiments.
[0030] The waterborne epoxy emulsion is purchased from Guangzhou Ge Mou New Materials Co., Ltd., with the product number GL 1900. Its solid content is 50 ± 2%, and the epoxy value is 0.17 ± 0.01 mol / 100g.
[0031] Example 1
[0032] An ultra-thin corrosion-resistant waterborne coating is composed of component A and component B in a mass ratio of 10:1.
[0033] The raw materials of Component A include: 400 g of waterborne epoxy emulsion, 300 g of zinc powder, 12 g of phosphoric acid, 10 g of graphene oxide, 1 g of γ-aminopropyltriethoxysilane, 10 g of BYK-333, 1 g of TEGO Foamex 825, 10 g of ammonium molybdate, and 1 g of Efka EFKA-3777.
[0034] Component B includes: 40 g of polyetheramine, 1 g of benzyldimethylamine, 1 g of 2.0-generation hyperbranched polyamidoamine, 5 g of dipropylene glycol butyl ether, and 20 g of deionized water.
[0035] The preparation method of the above ultra-thin corrosion-resistant waterborne coating includes the following steps:
[0036] S1. Immerse the zinc powder in 800 g of a phosphoric acid solution with a mass fraction of 1.5%, perform ultrasonic treatment at a temperature of 40 °C for 10 min, with an ultrasonic frequency of 35 kHz and an ultrasonic power of 400 W, centrifuge, wash with deionized water until neutral, vacuum dry at a temperature of 105 °C, and pulverize; add graphene oxide, γ-aminopropyltriethoxysilane, and 200 g of deionized water and mix, and ball mill at a speed of 150 r / min for 1 h to obtain composite zinc powder;
[0037] S2. Preheat the waterborne epoxy emulsion to 40 °C, adjust the pH value of the system to 8 - 9, add the composite zinc powder and BYK-333, raise the temperature to 60 °C and continue stirring for 1 h, with a stirring speed of 500 r / min, cool to room temperature, add TEGO Foamex 825, ammonium molybdate, and Efka EFKA-3777 and stir evenly, and filter to obtain Component A;
[0038] S3. Mix the polyetheramine, hyperbranched polyamidoamine, and benzyldimethylamine evenly, add dipropylene glycol butyl ether and deionized water and perform ultrasonic treatment for 20 min, with an ultrasonic frequency of 30 kHz and an ultrasonic power of 400 W, to obtain Component B.
[0039] Example 2
[0040] An ultra-thin corrosion-resistant waterborne coating is composed of Component A and Component B in a mass ratio of 10:2.
[0041] The raw materials of Component A include: 600 g of waterborne epoxy emulsion, 500 g of zinc powder, 36 g of phosphoric acid, 30 g of graphene oxide, 10 g of γ-aminopropyltriethoxysilane, 20 g of BYK-333, 10 g of TEGO Foamex 825, 30 g of ammonium molybdate, and 10 g of Efka EFKA-3777.
[0042] Component B includes: 60 g of polyetheramine, 3 g of benzyldimethylamine, 3 g of 4.0-generation hyperbranched polyamidoamine, 15 g of dipropylene glycol butyl ether, and 30 g of deionized water.
[0043] The preparation method of the above-mentioned ultra-thin corrosion-resistant waterborne coating comprises the following steps:
[0044] S1. Immerse zinc powder in 1200 g of phosphoric acid solution with a mass fraction of 3%, perform ultrasonic treatment at a temperature of 50 °C for 20 min, with an ultrasonic frequency of 40 kHz and an ultrasonic power of 500 W, centrifuge, wash with deionized water until neutral, vacuum dry at a temperature of 105 °C, and pulverize; add graphene oxide, γ-aminopropyltriethoxysilane, and 300 g of deionized water and mix, and ball mill at a speed of 250 r / min for 2 h to obtain composite zinc powder;
[0045] S2. Preheat the waterborne epoxy emulsion to 50 °C, adjust the pH value of the system to 8 - 9, add the composite zinc powder and BYK-333, raise the temperature to 65 °C and continue stirring for 3 h, with a stirring speed of 1000 r / min, cool to room temperature, add TEGO Foamex 825, ammonium molybdate, and Efka EFKA-3777 and stir evenly, and filter to obtain Component A;
[0046] S3. Mix polyetheramine, hyperbranched polyamidoamine, and benzyldimethylamine evenly, add dipropylene glycol butyl ether and deionized water and perform ultrasonic treatment for 40 min, with an ultrasonic frequency of 40 kHz and an ultrasonic power of 500 W to obtain Component B.
[0047] Example 3
[0048] An ultra-thin corrosion-resistant waterborne coating is composed of Component A and Component B in a mass ratio of 10:1.3.
[0049] The raw materials of Component A include: 550 g of waterborne epoxy emulsion, 350 g of zinc powder, 22 g of phosphoric acid, 25 g of graphene oxide, 3 g of γ-aminopropyltriethoxysilane, 18 g of BYK-333, 3 g of TEGO Foamex 825, 25 g of ammonium molybdate, and 2 g of Efka EFKA-3777.
[0050] Component B includes: 55 g of polyetheramine, 1.5 g of benzyldimethylamine, 1.5 g of 3.5-generation hyperbranched polyamidoamine, 12 g of dipropylene glycol butyl ether, and 22 g of deionized water.
[0051] The preparation method of the above-mentioned ultra-thin corrosion-resistant waterborne coating comprises the following steps:
[0052] S1. Immerse zinc powder in 1100 g of phosphoric acid solution with a mass fraction of 2%, perform ultrasonic treatment at a temperature of 48 °C for 12 min, with an ultrasonic frequency of 39 kHz and an ultrasonic power of 430 W, centrifuge, wash with deionized water until neutral, vacuum dry at a temperature of 105 °C, and pulverize; add graphene oxide, γ-aminopropyltriethoxysilane, and 280 g of deionized water and mix, and ball mill at a speed of 180 r / min for 100 min to obtain composite zinc powder;
[0053] S2. Preheat the aqueous epoxy emulsion to 42 °C, adjust the pH value of the system to 8 - 9, add composite zinc powder and BYK-333, raise the temperature to 63 °C and continue stirring for 1.5 h at a stirring speed of 900 r / min. Cool to room temperature, add TEGO Foamex 825, ammonium molybdate, and Efka EFKA-3777 and stir evenly. Filter to obtain Component A.
[0054] S3. Mix polyetheramine, hyperbranched polyamidoamine, and benzyldimethylamine evenly, add dipropylene glycol butyl ether and deionized water, and perform ultrasonic treatment for 25 min at an ultrasonic frequency of 39 kHz and an ultrasonic power of 420 W to obtain Component B.
[0055] Example 4
[0056] An ultra-thin corrosion-resistant aqueous coating is composed of Component A and Component B in a mass ratio of 10:1.7.
[0057] The raw materials of Component A include: 450 g of aqueous epoxy emulsion, 450 g of zinc powder, 22.5 g of phosphoric acid, 15 g of graphene oxide, 7 g of γ-aminopropyltriethoxysilane, 12 g of BYK-333, 7 g of TEGO Foamex 825, 15 g of ammonium molybdate, and 8 g of Efka EFKA-3777.
[0058] Component B includes: 45 g of polyetheramine, 2.5 g of benzyldimethylamine, 2.5 g of 2.5-generation hyperbranched polyamidoamine, 8 g of dipropylene glycol butyl ether, and 28 g of deionized water.
[0059] The preparation method of the above ultra-thin corrosion-resistant aqueous coating includes the following steps:
[0060] S1. Immerse the zinc powder in 900 g of a phosphoric acid solution with a mass fraction of 2.5%, perform ultrasonic treatment at a temperature of 42 °C for 18 min at an ultrasonic frequency of 36 kHz and an ultrasonic power of 470 W, centrifuge, wash with deionized water until neutral, vacuum dry at a temperature of 105 °C, and pulverize; add graphene oxide, γ-aminopropyltriethoxysilane, and 220 g of deionized water and mix, and perform ball milling at a speed of 220 r / min for 80 min to obtain composite zinc powder.
[0061] S2. Preheat the aqueous epoxy emulsion to 48 °C, adjust the pH value of the system to 8 - 9, add composite zinc powder and BYK-333, raise the temperature to 61 °C and continue stirring for 2.5 h at a stirring speed of 700 r / min. Cool to room temperature, add TEGO Foamex 825, ammonium molybdate, and Efka EFKA-3777 and stir evenly. Filter to obtain Component A.
[0062] S3. Mix polyetheramine, hyperbranched polyamidoamine, and benzyldimethylamine evenly, add dipropylene glycol butyl ether and deionized water, and perform ultrasonic treatment for 35 min at an ultrasonic frequency of 33 kHz and an ultrasonic power of 480 W to obtain Component B.
[0063] Example 5
[0064] An ultra-thin corrosion-resistant waterborne coating is composed of Component A and Component B in a mass ratio of 10:1.5.
[0065] The raw materials of Component A include: 500 g of waterborne epoxy emulsion, 400 g of zinc powder, 22 g of phosphoric acid, 20 g of graphene oxide, 5 g of γ-aminopropyltriethoxysilane, 15 g of BYK-333, 5 g of TEGO Foamex 825, 20 g of ammonium molybdate, and 5 g of Efka EFKA-3777.
[0066] Component B includes: 50 g of polyetheramine, 2 g of benzyldimethylamine, 2 g of 3.0-generation hyperbranched polyamidoamine, 10 g of dipropylene glycol butyl ether, and 25 g of deionized water.
[0067] The preparation method of the above ultra-thin corrosion-resistant waterborne coating includes the following steps:
[0068] S1. Immerse zinc powder in 1000 g of a phosphoric acid solution with a mass fraction of 2.2%, perform ultrasonic treatment at a temperature of 45°C for 15 min at an ultrasonic frequency of 37.5 kHz and an ultrasonic power of 450 W, centrifuge, wash with deionized water until neutral, vacuum dry at a temperature of 105°C, and pulverize; add graphene oxide, γ-aminopropyltriethoxysilane, and 250 g of deionized water and mix, and ball mill at a speed of 200 r / min for 90 min to obtain composite zinc powder;
[0069] S2. Preheat the waterborne epoxy emulsion to 45°C, adjust the pH value of the system to 8 - 9, add the composite zinc powder and BYK-333, raise the temperature to 62°C and continue stirring for 2 h at a stirring speed of 800 r / min, cool to room temperature, add TEGO Foamex 825, ammonium molybdate, and Efka EFKA-3777 and stir evenly, and filter to obtain Component A;
[0070] S3. Mix polyetheramine, hyperbranched polyamidoamine, and benzyldimethylamine evenly, add dipropylene glycol butyl ether and deionized water, and perform ultrasonic treatment for 30 min at an ultrasonic frequency of 36 kHz and an ultrasonic power of 450 W to obtain Component B.
[0071] Comparative Example 1
[0072] An ultra-thin corrosion-resistant waterborne coating is composed of Component A and Component B in a mass ratio of 10:1.5.
[0073] The raw materials of Component A include: 500 g of waterborne epoxy emulsion, 400 g of zinc powder, 22 g of phosphoric acid, 25 g of graphene oxide, 15 g of BYK-333, 5 g of TEGO Foamex 825, 20 g of ammonium molybdate, and 5 g of EFKA-3777.
[0074] Component B includes: 50 g of polyetheramine, 2 g of benzyldimethylamine, 2 g of 3.0-generation hyperbranched polyamidoamine, 10 g of dipropylene glycol butyl ether, and 25 g of deionized water.
[0075] The preparation method of the above ultra-thin corrosion-resistant waterborne coating includes the following steps:
[0076] S1. Immerse the zinc powder in 1000 g of phosphoric acid solution with a mass fraction of 2.2%, perform ultrasonic treatment at a temperature of 45 °C for 15 min, with an ultrasonic frequency of 37.5 kHz and an ultrasonic power of 450 W, centrifuge, wash with deionized water until neutral, vacuum dry at a temperature of 105 °C, and pulverize; add graphene oxide and 250 g of deionized water and mix, and ball mill at a speed of 200 r / min for 90 min to obtain composite zinc powder;
[0077] S2. Preheat the waterborne epoxy emulsion to 45 °C, adjust the pH value of the system to 8 - 9, add the composite zinc powder and BYK-333, raise the temperature to 62 °C and continue stirring for 2 h, with a stirring speed of 800 r / min, cool to room temperature, add TEGO Foamex 825, ammonium molybdate, and EFKA-3777 and stir evenly, and filter to obtain Component A;
[0078] S3. Mix the polyetheramine, hyperbranched polyamidoamine, and benzyldimethylamine evenly, add dipropylene glycol butyl ether and deionized water and perform ultrasonic treatment for 30 min, with an ultrasonic frequency of 36 kHz and an ultrasonic power of 450 W, to obtain Component B.
[0079] Comparative Example 2
[0080] An ultra-thin corrosion-resistant waterborne coating is composed of Component A and Component B in a mass ratio of 10:1.5.
[0081] The raw materials of Component A include: 500 g of waterborne epoxy emulsion, 400 g of zinc powder, 22 g of phosphoric acid, 20 g of graphene oxide, 5 g of γ-aminopropyltriethoxysilane, 15 g of BYK-333, 5 g of TEGO Foamex 825, 20 g of ammonium molybdate, and 5 g of EFKA-3777.
[0082] Component B includes: 50 g of polyetheramine, 4 g of benzyldimethylamine, 10 g of dipropylene glycol butyl ether, and 25 g of deionized water.
[0083] The preparation method of the above ultra-thin corrosion-resistant waterborne coating includes the following steps:
[0084] S1. Immerse zinc powder in 1000 g of phosphoric acid solution with a mass fraction of 2.2%, perform ultrasonic treatment at a temperature of 45 °C for 15 min, with an ultrasonic frequency of 37.5 kHz and an ultrasonic power of 450 W, centrifuge, wash with deionized water until neutral, vacuum dry at a temperature of 105 °C, and pulverize; add graphene oxide, γ-aminopropyltriethoxysilane, and 250 g of deionized water and mix, and ball mill at a speed of 200 r / min for 90 min to obtain composite zinc powder;
[0085] S2. Preheat the waterborne epoxy emulsion to 45 °C, adjust the pH value of the system to 8 - 9, add the composite zinc powder and BYK-333, raise the temperature to 62 °C and continue stirring for 2 h, with a stirring speed of 800 r / min, cool to room temperature, add TEGO Foamex 825, ammonium molybdate, and Efka EFKA-3777 and stir evenly, and filter to obtain Component A;
[0086] S3. Mix polyetheramine and benzyldimethylamine evenly, add dipropylene glycol butyl ether and deionized water and perform ultrasonic treatment for 30 min, with an ultrasonic frequency of 36 kHz and an ultrasonic power of 450 W to obtain Component B.
[0087] Store Component A in the ultra-thin corrosion-resistant waterborne coatings obtained in Example 5 and Comparative Examples 1 - 2 at room temperature for 6 months. It is found that Component A in Example 5 and Comparative Example 2 did not show delamination or precipitation after 6 months of storage at room temperature; while Component A in Comparative Example 1 showed delamination and precipitation only after 2 months of storage at room temperature.
[0088] Spray the ultra-thin corrosion-resistant waterborne coatings obtained in Example 5 and Comparative Examples 1 - 2 as follows: Use a steel plate of grade Q195 (cleaned and polished) as the substrate, mix Component A and Component B evenly, spray 3 times on the area to be coated, with a film thickness of 25 μm each time, and the total film thickness obtained is 75 μm, and bake and cure at 75 °C for 20 min.
[0089] Refer to GB / T 1732-2020 "Method for the Determination of Impact Resistance of Films" to measure the impact resistance of the above-mentioned films, and use the maximum height without cracks to characterize the size of the impact resistance. Refer to GB / T 5210-2006 "Pull-off Adhesion Test for Paints and Varnishes" to measure the adhesion of the above-mentioned films.
[0090] As Figure 1 shown, the impact resistance and adhesion of the film prepared with the ultra-thin corrosion-resistant waterborne coating obtained in Example 5 are both the best, superior to Comparative Examples 1 - 2 (P < 0.05).
[0091] Refer to GB / T 1733-1993 "Determination of Water Resistance of Paint Films" to test the water resistance, acid resistance (10% hydrochloric acid), and alkali resistance (30% sodium hydroxide solution) of each group of paint films. Refer to GB / T 10125-2012 "Artificial Atmosphere Corrosion Test - Salt Spray Test" to test the salt spray resistance of each group of paint films. The results are shown in Table 1.
[0092] Table 1 Results of the ultra-thin corrosion-resistant waterborne paint films obtained in Example 5 and Comparative Examples 1-2
[0093]
[0094] It can be found from Table 1 that the paint film prepared from the ultra-thin corrosion-resistant waterborne paint obtained in Example 5 has excellent water resistance and corrosion resistance.
[0095] Refer to ASTM D7027-05 "Test Method for Scratch Recovery of Plastics", and use a multi-finger scratching tester to scratch the above-mentioned paint films of each group. The scratching tip is made of stainless steel with a diameter of 1 mm. The applied load during the test is 15 N, the scratching speed is 100 mm / s, and the scratch length is 100 mm. Use a laser confocal microscope to observe the surface scratch width, then let it stand in an environment of 25°C and 80% RH for 24 h, and observe the surface scratch width again to calculate the self-healing rate.
[0096] Self-healing rate = surface scratch width after standing at room temperature for 24 h ÷ original surface scratch width × 100%
[0097] As Figure 2 shown, the paint film prepared from the ultra-thin corrosion-resistant waterborne paint in Example 5 has the highest self-healing rate and is higher than 90%, which is better than that of Comparative Examples 1-2 (P < 0.05), indicating that the ultra-thin corrosion-resistant waterborne paint obtained in the present invention has good self-healing performance.
[0098] The above is only the preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and all should be covered by the protection scope of the present invention.
Claims
1. An ultra-thin corrosion-resistant water-based coating, characterized in that: It is composed of component A and component B in a mass ratio of 10:1-2; The raw materials of component A include, by mass: 40-60 parts of waterborne epoxy emulsion, 30-50 parts of zinc powder, 1.2-3.6 parts of phosphoric acid, 1-3 parts of graphene oxide, 0.1-1 parts of γ-aminopropyltriethoxysilane, 1-2 parts of dispersant, 0.1-1 parts of defoamer, 1-3 parts of corrosion inhibitor, and 0.1-1 parts of leveling agent; Component B includes, by mass: 40-60 parts of curing agent, 1-3 parts of accelerator, 1-3 parts of hyperbranched polyamide amine, 5-15 parts of cosolvent, and 20-30 parts of water.
2. The ultra-thin corrosion-resistant water-based coating according to claim 1, characterized in that: The solid content of the waterborne epoxy emulsion is 45-55%, and the epoxy value is 0.1-0.2 mol / 100g.
3. The ultra-thin corrosion-resistant water-based coating according to claim 1, characterized in that: The dispersant is polyether modified siloxane; the leveling agent is fluorocarbon surfactant.
4. The ultra-thin corrosion-resistant water-based coating according to claim 1, characterized in that: Corrosion inhibitors include: Ammonium molybdate.
5. The ultra-thin corrosion-resistant water-based coating according to claim 1, characterized in that: The accelerator is benzyl dimethylamine; the cosolvent is dipropylene glycol butyl ether.
6. The ultra-thin corrosion-resistant water-based coating according to claim 1, characterized in that: The generation number of the hyperbranched polyamidoamine is 2.0-4.0 generations.
7. A method for preparing the ultra-thin corrosion-resistant water-based coating according to any one of claims 1 to 6, characterized in that: The steps include: S1. Immerse zinc powder in a phosphoric acid aqueous solution, perform ultrasonic treatment at 40-50° C. for 10-20 min, centrifuge, wash until neutral, vacuum dry, and crush; add graphene oxide, γ-aminopropyltriethoxysilane, and water, mix, and ball mill for 1-2 h to obtain composite zinc powder; S2. Preheat the waterborne epoxy emulsion to 40-50°C, adjust the pH value of the system to 8-9, add composite zinc powder and dispersant, raise the temperature to 60-65°C and continue stirring for 1-3h, cool to room temperature, add defoamer, corrosion inhibitor and leveling agent, stir evenly, and filter to obtain component A; S3, mixing the curing agent, hyperbranched polyamide amine and accelerator evenly, adding a cosolvent and water, and ultrasonically treating for 20-40 minutes to obtain component B.
8. The method for preparing the ultra-thin corrosion-resistant water-based coating according to claim 7, characterized in that: In S1, the ultrasonic frequency is 35-40kHz, the ultrasonic power is 400-500W, and the ball milling speed is 150-250r / min.
9. The method for preparing the ultra-thin corrosion-resistant water-based coating according to claim 7, characterized in that: In S3, the ultrasonic frequency is 30-40kHz and the ultrasonic power is 400-500W.
10. A method for using the ultra-thin corrosion-resistant water-based coating according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: mixing component A and component B evenly, spraying the components to be coated for several times, each time forming a film with a thickness of 15-25 μm, and obtaining a total coating film with a thickness of 60-75 μm, and baking and curing at 70-80°C.
Citation Information
Patent Citations
Graphene composite anti-rust pigment and preparation method thereof
CN108864790A
Coupling method for waterborne epoxy coating and graphene oxide composite coating interfacial hyperbranched polyamide
CN108997886A
Water-based high-solid-content two-component epoxy paint and preparation method thereof
CN113637385A
Modified cold zinc spraying coating and preparation method thereof
CN116082943A
Building fireproof coating and preparation method thereof
CN116970325A
Cited By
Water-based environment-friendly two-component epoxy resin coating and preparation method thereof
CN120648321A
Thin-coating high-salt-mist-resistant water-based anticorrosive paint and preparation method thereof
CN121930717A